Evaluation of high-dose insulin/euglycemia therapy for suspected β-blocker or calcium channel blocker overdose following guideline implementation. (19th November 2021) - Schult, Rachel F; Nacca, Nicholas; Grannell, Tori L; Jorgensen, Rachel M; Acquisto, Nicole M
Abstract: Purpose: High-dose insulin/euglycemia (HDIE) is targeted therapy for β-blocker and calcium channel blocker overdose. A guideline using concentrated insulin infusions (20 units/mL), aggressive monitoring, and supportive recommendations was implemented. We sought to evaluate safety before and after HDIE guideline implementation and describe the patient population, insulin doses, supplemental dextrose, vasopressor use, hospital and intensive care unit (ICU) lengths of stay, and mortality. Methods: Retrospective review was performed of patients receiving HDIE before and after guideline implementation at an academic medical center and community hospital from March 2011 through December 2019. Information on patient and overdose demographics, ingestion data, vital signs, interventions, adverse events, and disposition was collected. Data are presented descriptively with comparisons using Mann-Whitney U analysis and Fisher's exact tests. Results: During the study period, 27 patients were treated with HDIE, 10 before guideline implementation (37%; mean [SD] initial insulin dose, 0.49 [0.35] units/kg/h; mean [SD] maximum insulin dose, 2.25 [3.29] units/kg/h; median [interquartile range] duration, 10 [5.5-18.75] hours) and 17 after guideline implementation (63%; mean [SD] initial insulin dose, 1.01 [0.34] units/kg/h; mean [SD] maximum insulin dose, 2.99 [5.05] unit/kg/h; median [interquartile range] duration, 16 [11.5-37] hours). Hypoglycemia, hypokalemia, and volume overload occurred in 80% vs 29% ( P = 0.018), 40% vs 53% ( P = 0.69), and 50% vs 65% ( P = 0.69) of patients in the preguideline vs postguideline group, respectively. Most patients received an initial insulin bolus (85%; mean [SD], 70.3 [21.8] units, 0.9 [0.26] units/kg) and vasopressor infusion (85%). More postguideline patients received a dextrose infusion with a concentration of 20% or higher (93% vs 50%, P = 0.015). There were no differences in cardiac arrest, in-hospital mortality, or hospital or ICU length of stay between the groups. Conclusion: Hypoglycemia was reduced using an HDIE guideline and concentrated insulin.